2014
DOI: 10.1155/2014/196353
|View full text |Cite|
|
Sign up to set email alerts
|

Fear Processing in Dental Phobia during Crossmodal Symptom Provocation: An fMRI Study

Abstract: While previous studies successfully identified the core neural substrates of the animal subtype of specific phobia, only few and inconsistent research is available for dental phobia. These findings might partly relate to the fact that, typically, visual stimuli were employed. The current study aimed to investigate the influence of stimulus modality on neural fear processing in dental phobia. Thirteen dental phobics (DP) and thirteen healthy controls (HC) attended a block-design functional magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 44 publications
(72 reference statements)
1
31
0
Order By: Relevance
“…The 31 studies included 564 patients with SP and 485 HC (Brinkmann, Poller, Herrmann, Miltner, & Straube, ; Britton et al, ; Caseras, Giampietro, et al, ; Caseras, Mataix‐Cols, et al, ; Dilger et al, ; Goossens, Schruers, Peeters, Griez, & Sunaert, a; Goossens et al, 2007b Halsband & Wolf, ; Hermann et al, ; Hilbert, Evens, Maslowski, Wittchen, & Lueken, ; Killgore et al, ; Lipka et al, ; Lipka, Miltner, & Straube, ; Lueken et al, , ; Michalowski et al, ; Munsterkotter et al, ; Scharmuller et al, ; Schienle et al, ; Schienle, Schafer, Walter, Stark, & Vaitl, ; Schienle, Scharmuller, Leutgeb, Schafer, & Stark, ; Schweckendiek et al, ; Straube, Glauer, et al, ; Straube, Lipka, Sauer, Mothes‐Lasch, & Miltner, ; Straube et al, ; Straube, Mentzel, & Miltner, , ; Wendt, Lotze, Weike, Hosten, & Hamm, ; Wiemer et al, ; Wright et al, ; Zilverstand, Sorger, Kaemingk, & Goebel, ). In six studies, two different subtypes of phobias were considered, with the most studied (24 out of 31) subtype being spider phobia; dental phobia was evaluated in six studies, whereas small animal and blood/injection subtypes in four and three studies, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 31 studies included 564 patients with SP and 485 HC (Brinkmann, Poller, Herrmann, Miltner, & Straube, ; Britton et al, ; Caseras, Giampietro, et al, ; Caseras, Mataix‐Cols, et al, ; Dilger et al, ; Goossens, Schruers, Peeters, Griez, & Sunaert, a; Goossens et al, 2007b Halsband & Wolf, ; Hermann et al, ; Hilbert, Evens, Maslowski, Wittchen, & Lueken, ; Killgore et al, ; Lipka et al, ; Lipka, Miltner, & Straube, ; Lueken et al, , ; Michalowski et al, ; Munsterkotter et al, ; Scharmuller et al, ; Schienle et al, ; Schienle, Schafer, Walter, Stark, & Vaitl, ; Schienle, Scharmuller, Leutgeb, Schafer, & Stark, ; Schweckendiek et al, ; Straube, Glauer, et al, ; Straube, Lipka, Sauer, Mothes‐Lasch, & Miltner, ; Straube et al, ; Straube, Mentzel, & Miltner, , ; Wendt, Lotze, Weike, Hosten, & Hamm, ; Wiemer et al, ; Wright et al, ; Zilverstand, Sorger, Kaemingk, & Goebel, ). In six studies, two different subtypes of phobias were considered, with the most studied (24 out of 31) subtype being spider phobia; dental phobia was evaluated in six studies, whereas small animal and blood/injection subtypes in four and three studies, respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The first subsample of subjects took part in: Straube, Glauer, et al (); Straube et al (, ); Straube, Mentzel, et al (). The second one was included in: Lipka et al (, ); Straube et al (), and the third subsample participated both in Hilbert et al () and Lueken et al ().…”
Section: Resultsmentioning
confidence: 99%
“…The thalamus is implicated in sensory integration, and functional imaging studies revealed increased activation in the thalamus in response to phobic-related and threat stimuli in patients with SAD, 24 , 25 blood-injection-injury phobia, 26 dental phobia, 27 spider phobia, 28 snake phobia, 29 and PTSD. 30 Contrary to these findings, one study reported that dental phobics did not demonstrate increased activation in thalamus to phobic images.…”
Section: Sensory Processing Regionsmentioning
confidence: 99%
“…Recent functional imaging studies revealed insula hyperactivation to threat in patients with SP, 27 29 , 71 SAD, 36 , 50 , 52 , 65 , 72 , 73 and PTSD 30 , 54 , 74 77 compared with controls. The degree of insula hyperactivation was positively correlated with symptom severity in SAD.…”
Section: Emotion Generating/processing Regionsmentioning
confidence: 99%
“…Only one study using auditory stimuli (compared to video sequence or pictures) found higher activation in dental phobia patients compared to healthy controls. This heightened activation occurred in areas associated with phobia‐related fear, but again, no increase in autonomic arousal has been observed (Hilbert, Evens, Maslowski, Wittchen, & Lueken, ).…”
Section: Discussionmentioning
confidence: 97%